THE DIFFICULT SCIENCE IN MAKING SCIENCE DIFFICULT - Eduardo de Paiva Gonçalves, Sergio (Revista Científica do CRO-RJ (Rio de Janeiro Dental Journal), 2019)
What to do when your manuscript is violently debased by the reviewers of a journal? What to understand of such forceful affront to your knowledge and ethical principles? Why is it necessary to look abroad for quality and creativity when these qualities areinherent to Brazilians? Why does the feeling of “Colony” rule over the country that occupies the second place in scientific publication in the area of Dentistry? Why do regulators of the Brazilian academic management system themselves devalue Brazilian journals and maintain unclear rules policy1? Amazingly, these are questions and reflections that are apparently not restricted to our area of knowledge.